Explore Teachers' Skills in Developing Lesson Plan and Assessment That Oriented on Higher Order Thinking Skills (HOTS) - Irma Rahma Suwarma; Sera Apriyani (Journal of Innovation in Educational and Cultural Research, 2022)
In 2018, the Indonesian Ministry of Education issued a new policy related to the development of learning oriented towards a Higher Order Thinking Skill (HOTS) approach at the primary and secondary school levels. This learning development is expected to be able to improve the achievement of Indonesian students in international competitions such as PISA and TIMSS. This program was developed following the policy direction of the Ministry of Education and Culture which in 2018 has integrated Strengthening Character Education and learning oriented to ‘HOTS’. Recently, the program is integrated into the MBKM program, where Universitas Pendidikan Indonesia (UPI) a university that produces educators decides to take a role in developing HOTS. This study aims to identify teacher skills in developing lesson plans and HOTS-oriented assessments. This is a case study research. A mixed-method design was used in this study as a way to analyse the teacher training process and the outcomes of the training. The sample of this research is science teacher at the sample school in Bandung. The results of the study show that the development skills of teachers' lesson plans are in the intermediate category, but not all lesson plans describe activities on ‘intermediate’ category. Therefore, further training and coaching is needed.